The effect of milling time in production of urea compound by ball milling technique: article / Syasya Zulkipli and Dr. Atikah Kadri - Zulkipli, Syasya; Kadri, Atikah (2018)
The aim of the paper was to investigate the optimum milling time in production of urea compound through ball milling techniques by varying the time taken for the tendency of urea to avoid become hygroscopic in order to generate quality urea fertilizer that will not cause hydrate formation in the presence of water that will make the mixture wet and sticky. The effect of the milling time and mixture content was investigated. Physical observation showing that with prolonging the milling time, the mixture becoming from powder form to clumped. Through FTIR, the milling process of 2 minutes recorded moisture loss of 21.7% and 4.34 mg weight loss, while 4 minutes is at 24.01% with 4.80 mg, 6 minutes at 30.46% and 6.09 mg, 10 minutes is at 28.4% and 5.70 mg and 12 minutes at 25.28% and 5.06 mg of moisture loss and weight loss respectively for all of the samples that being milled. The ideal and optimum milling process for the urea calcium phosphate is to be suggested at 2 minutes with the lowest moisture and weight loss.